2008
DOI: 10.1103/physrevb.77.064408
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field dependence of the ferroelectric polarization and spin-lattice coupling in multiferroicMnWO4

Abstract: The magnetic-field dependence of the ferroelectric polarization and the spin-lattice coupling in multiferroic MnWO 4 have been investigated. The ferroelectric transition from the low temperature paraelectric phase occurs when the magnetic field is applied along the a, c, and the spin easy axes. The ferroelectric polarization in the magnetic field along the a and the c axis shows a contrasting behavior depending on the field direction, possibly reflecting the relative configuration between the crystallographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 23 publications
8
51
0
Order By: Relevance
“…9,11,12 One of the advantages of studying MnWO 4 is that it has only one kind of magnetic ion (Mn 2+ ), whereas other multiferroic oxides usually have multiple magnetic ions, thus hindering investigation of their magnetic properties. With the advantage of single magnetic ion, we are provided with a clear window into the electromagnetic coupling behavior and are able to make simple analyses of the magnetic field dependence and SOC effects.…”
Section: 10mentioning
confidence: 99%
“…9,11,12 One of the advantages of studying MnWO 4 is that it has only one kind of magnetic ion (Mn 2+ ), whereas other multiferroic oxides usually have multiple magnetic ions, thus hindering investigation of their magnetic properties. With the advantage of single magnetic ion, we are provided with a clear window into the electromagnetic coupling behavior and are able to make simple analyses of the magnetic field dependence and SOC effects.…”
Section: 10mentioning
confidence: 99%
“…[4][5][6] Recent work has demonstrated that the ferroelectric and spin-spiral orders coexist and are intimately coupled in this material. [4][5][6][7][8][9][10][11] MnWO 4 undergoes three magnetic phase transitions in zero magnetic field below 14 K (Figure 1). 12 With decreasing temperature, MnWO 4 first transforms from a paramagnetic (PM) state to a collinear spin sinusoidal state (AF3) at T N ≈ 13.5 K, then to a tilted elliptical spiral spin state (AF2) at T 2 ≈ 12.3 K, and eventually to a up-up-down-down collinear spin structure (AF1) at T 1 ≈ 8.0 K. The magnetic structures of the AF3 and AF2 states are ICM to the lattice spacing with propagation vector k = (-0.214, 0.5, 0.457), while that of the AF1 state is commensurate (CM) with propagation vector k = (-0.25, 0.5, 0.5).…”
Section: Introductionmentioning
confidence: 99%
“…The remanent polarization of about 39 C / m 2 at 10 K agrees well with the reported forced polarization in this material. 11,12 Remanent polarization ͑Fig. 2͒ and ferroelectric coercive force ͑inset of Fig.…”
mentioning
confidence: 99%